Supply Chain Management: Manufacturing in Blockwork System - Farul Afendi Bahari; Mohamed Nor Azhari Azman; Mohd Nasrun Mohd Nawi; Abdul Rahman Ayub; Nurul Fadly Habidin (International Journal of Supply Chain Management, 2017)
Industrialized building system has been introduced in Malaysia as an initiative to promote the construction sector. One of the systems that are in use IBS is blockwork system which is an evolution of the use of conventional brick. Making the block has several parts or processes that must be taken to produce the component. Planning the layout of a manufacturing industry should be implemented taking into account all needs ranging from suppliers of raw materials until the final product to be distributed to customers. Supply chain management definitions focused on the physical movement of goods, i.e. total flow of materials from suppliers to end customers. From this we see SCM can help for designing the plant layout design. Workflow in and out of the raw material suppliers and the final product to the customer and facility management is necessary to ensure that employees or machine operator can perform the work safely and comfortably. The result shows that key management approach, proper planning and organized is the key facilitate the workflow of managing the layout of the production equipment and support services that are the backbone of a manufacturing industry.